Revealing the competitive effect of N2 and H2O towards CO2 adsorption in N-rich ordered mesoporous carbons. (March 2023) - Maruccia, E.; Piovano, A.; Lourenço, M.A.O.; Priamushko, T.; Cavallo, M.; Bocchini, S.; Bonino, F.; Pirri, F.C.; Kleitz, F.; Gerbaldi, C.
Abstract: The incorporation of heteroatoms improves CO2 adsorption on carbon-based materials, but it can also provide some hydrophilic character to the bare-carbon frameworks, making the hypothesis of competitive CO2 /H2 O adsorption not negligible. In this respect, the CO2 capture is here evaluated through a deep characterization of the sorption properties of N-rich ordered mesoporous carbons under dry and moisture conditions, and in CO2 /N2 gas mixtures. The nanocasting strategy is used to obtain N-rich CMK-3-type carbons in one pot by impregnating D-glucosamine hydrochloride, a carbon/nitrogen source, into an SBA-15 silica template followed by pyrolysis treatment at 600, 750, and 900 °C. The fine-tuning of the pyrolysis treatment aims to find the right proportion of micropores and N content, which are important features for selective CO2 adsorption. The highest surface amount of N (11.3 at.%), in particular of the pyridinic type, enhances the CO2 /N2 selectivity (1.03 mmol/g of adsorbed CO2 from a 20% CO2 in N2 ), but also the undesired increment in the H2 O uptake. CO2 uptake under competitive CO2 /H2 O conditions is better preserved with 8.3 at.% of surface nitrogen (1.55, 1.52, 0.61, and 0.89 mmol/g of CO2 at a relative humidity of 0, 25, 50, and 75%, respectively). Interestingly, the N-CMK-3 materials retain their capture properties over repetitive adsorption-desorption cycles in pure CO2 . In this respect, a TGA-FTIR study is performed to monitor the reusability of the sorbents after CO2 capture from moist flue gases to assess the effectiveness of the reactivation procedure towards the removal of the adsorbed species. Graphical abstract: Image 1 Highlights: Nanocasting strategy in "one pot" to N-rich CMK-3 ordered mesoporous carbon CO2 sorbents. CO2 uptake tuned by the pyrolysis of the D-glucosamine precursor. Pyrolysis at 750 °C optimal compromise for selectivity/uptake. Higher content of pyridinic nitrogen enhances CO2 /N2 selectivity. CO2 /H2 O competition is adjustable by slightly reducing N content/H2 O affinity.